Economic security of Bosnia and Herzegovina as part of the national security system - Rebić, Mladen; Antić, Vladimir (Anali Ekonomskog fakulteta u Subotici, 2022)
Due to the specifics of the political and economic system in Bosnia and Herzegovina, in the recent history of the country it has not been possible to comprehensively and seriously approach the problem and challenges of economic security. The given circumstances reinforce the need for research and analysis of economic security in BiH in order to show the real situation. This paper analyzes economic security as a part of national security, with the help of relevant indicators, and then the connection of economic security with the economic development of BiH. For research purposes, methods of analysis, synthesis, compilation, correlation and linear regression were applied. The aim of the research is an empirical analysis of economic security indicators in terms of determining the degree of interconnection of key variables of economic security (public debt, availability of financial resources, technological progress, investment in fixed assets, unemployment, military investment, foreign exchange reserves, budget deficit, GDP growth rate, etc.) for the period from 2008 to 2018. The results of the research clearly revelas that economic and national security are mutuallyinterrelated, and that economic security is a precondition for national security, which confirms the main hypothesis of this paper.